Application of external flood probabilistic safety assessment methodology to Prototype Fast Breeder Reactor. Issue 4 (2nd October 2022) - Ramakrishnan, M.; Sharma, Pramod Kumar; Roshan, A. D.; Pisharady, A. S.; Raj, Magesh Mari; Chithira, P.; Arul, A. John; Bishnoi, L. R.
ABSTRACT: This paper presents the methodology adopted, accident sequence analysis and salient results from the external flood probabilistic safety analysis exercise for Prototype Fast Breeder Reactor. The major steps performed are the probabilistic hazard estimation, fragility computation, system reliability modelling and risk quantification. The hazard analysis has been performed for rainfall, storm surge and tsunami as typically associated with a coastal site, from which correlation function relating flood level to the annual exceedance frequency is estimated. The fragility analysis of different safety systems is estimated by considering submergence mode of failure using step fragility functions. The secondary effects of flood such as debris impact, load falling and flood-induced sodium fires are not considered. The human reliability analysis of manual operations necessary for plant safety is done for the control room as well as onsite actions. The challenges encountered during the analysis, salient results and uncertainties involved are presented with inferences. Abbreviations: AHX: air heat exchanger; CDF: core damage frequency; EFPSA: external flood probabilistic safety assessment; EL: elevation levels; EOP: emergency operation procedure; ET: event tree; FT: fault tree; HRA: human reliability analysis; IE: initiating events; NPP: nuclear power plant; OGDHRS: operation grade decay heat removal system; PFBR: prototype fast breeder reactor; POT: peak over threshold; PSA: probabilistic safety assessment; PTHA: probabilistic tsunami hazard assessment; RY: reactor year; RCB: reactor containment building; RP: return period; SGDHRS: safety grade decay heat removal system; SSC: structures, systems and components